2014
DOI: 10.1002/2013jd020799
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical characteristics of MJO convection over the Indian Ocean during DYNAMO

Abstract: The microphysical characteristics of precipitating convection occurring in various stages of the Madden-Julian Oscillation (MJO) over the Indian Ocean are determined from data obtained from the National Center for Atmospheric Research dual-polarimetric Doppler S-band radar, S-PolKa, deployed as part of the Dynamics of the MJO (DYNAMO) field experiment. Active MJO events with increased rainfall occurred in October, November, and December 2011. During each of these active MJO phases, in addition to enhanced rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 44 publications
8
76
2
Order By: Relevance
“…Johnson et al (1999) showed that tropical convection can be roughly separated into three categories: shallow cumulus with echo-top heights below 4 km, congestus with echo-top heights between 5 and 9 km, and cumulonimbus with echo tops above 10 km. Zuluaga and Houze (2013), Rowe and Houze (2014), and Xu and Rutledge (2014), using CINDY/DYNAMO data, and Riley et al (2011) and Barnes and Houze (2013), using CloudSat and TRMM observations, showed that all types of convective clouds can be observed during all phases of the MJO and that their relative proportions change with time. Any radar scene is thus likely to be a mix of convective clouds that certainly have different impacts on their environmental moisture: shallow convection is likely to moisten the first few kilometers of the atmosphere, whereas deep convection tends to dry it (e.g., Schumacher et al 2008).…”
Section: B In Situ Moisture Variation Compositesmentioning
confidence: 97%
“…Johnson et al (1999) showed that tropical convection can be roughly separated into three categories: shallow cumulus with echo-top heights below 4 km, congestus with echo-top heights between 5 and 9 km, and cumulonimbus with echo tops above 10 km. Zuluaga and Houze (2013), Rowe and Houze (2014), and Xu and Rutledge (2014), using CINDY/DYNAMO data, and Riley et al (2011) and Barnes and Houze (2013), using CloudSat and TRMM observations, showed that all types of convective clouds can be observed during all phases of the MJO and that their relative proportions change with time. Any radar scene is thus likely to be a mix of convective clouds that certainly have different impacts on their environmental moisture: shallow convection is likely to moisten the first few kilometers of the atmosphere, whereas deep convection tends to dry it (e.g., Schumacher et al 2008).…”
Section: B In Situ Moisture Variation Compositesmentioning
confidence: 97%
“…(Only information from the S band is employed in this study.) The details of S-PolKa data quality-control and fieldinstrumentation management can be found at https:// www.eol.ucar.edu/instrumentation/remote-sensing/s-pol and in prior studies (Powell and Houze 2013;Zuluaga and Houze 2013;Rowe and Houze 2014). When viewing S-PolKa data in this study, the caveat that the S-PolKa sampling region is far smaller than and on the corner of the northern sounding array must be considered.…”
Section: B Radar Cloud Measurementsmentioning
confidence: 99%
“…Therefore, what are retained are boundary layer-based clouds and highbased clouds with contiguous detectable rain shafts. During suppressed periods, when rainfall is minimal and stratiform systems rare, these echo features are dominated by boundary layer-based convective clouds (Barnes and Houze 2013;Powell and Houze 2013;Zuluaga and Houze 2013;Rowe and Houze 2014).…”
Section: B Radar Cloud Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zuluaga and Houze (2013) showed further how the number of MCSs is modulated by synoptic-scale waves during active periods. Rowe and Houze (2014) have examined the microphysical structures of the MCSs during active MJO periods. Guy and Jorgensen (2014) analyzed DYNAMO aircraft data and found broad echo-top-height distributions in MCSs during the MJO active period.…”
Section: Introductionmentioning
confidence: 99%